Effect of Personalisation of Instruction on Students’ Motivation to learn Mathematics Word Problems in Nigeria - Adeneye Olarewaju Awofala (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
This study investigated the effect of personalisation of instruction on the motivation to learn mathematics word problems of 450 senior secondary students in Nigeria within the blueprint of quasi-experimental research of Solomon Four non-equivalent control group design. It also examined the influence of gender on motivation to learn mathematics word problems and personalisation was accomplished by incorporating selected information with students‟ personal preferences into their mathematics word problems. Motivation to learn mathematics word problems was measured by the mathematics word problems motivation questionnaire and data collected for the study were analysed using the independent samples t-test and one way ANOVA. The results showed significant main effect of personalization of instruction on students‟ motivation to learn mathematics word problems whereas no significant main effect of gender was found on the dependent measure.